Photocatalytic Process Using Green Iron Nanoparticles for azo dye degradation from aqueous solution - احمد خسروی بغداده; taher shahryari; rasol khosravi (Mashhad University of Medical Sciences, 2020)
Background and purpose: Today, environmental pollution is a major problem for human life. Dye is one of the most important environment pollutants that is found in the industrial wastewater, especially in the textile industry wastewater. Therefore, the aim of this study was to evaluate the photocatalytic effect of green iron nanoparticles as catalyst for Reactive red 198 dye degradation in photocatalytic process. Materials and Methods: This study was performed laboratory using a batch reactor under UV A irradiation. In this study, the effect of different variables including pH (3-11), dye concentration (10-100 mg / l), catalyst dosage (0.25-3 g/l) and contact time (2-60 min) were investigated. The characterization of prepared nanoparticles were studied using different techniques such as TEM, FESEM and FTIR analysis. The obtained data were analyzed by Excel software. Results :Also, the photocatalytic tests showed high performance of NPs for dye degradation as catalyst in photocatalytic process. The highest removal efficiency achieved 96.2% at pH 3, catalyst dosage 1.5 g / L, contact time 15 min, and for dye concentration 25 mg / L. Conclusion :Additionally the results show that the photocatalytic process using green iron nanoparticles can be used with a suitable function to removal of reactive red 198 from aqueous solutions.